Menginterogasi Budaya: Memperkarakan Metodologi dalam Kajian Budaya - Budi Irawanto (Jurnal Komunikasi, 2008)
Methodology in cultural studies has triggered some conflicting discourses hence it has become harder, not easier, to be pined down and defined neatly. Since its inception cultural studies was dubbed as “an intellectual guerrilla” against the rigidity of disciplines in the academia. Further, in cultural studies knowledge is perceived as a practice rather than a sum of abstract propositions or general objective laws. This article argues that methodology in cultural studies is far to be “objective” (as defined by the positivist approach) since it context-bonded influenced by social position, historical moment and particular political agendas.